Rubiano Muñoz, Rafael. Press and tradition. The image of Spain in the work of Miguel Antonio Caro (2012)
This book is the result of the project Politics and intellectuals: the image of Spain in the nineteenth century. "The general research was funded by the Carolina Foundation and the University of Antioquia, and focused on the study of the reception of Spai